First detection of canine parvovirus 2b DNA in a crab-eating fox pup (Cerdocyon thous, Linnaeus, 1766) - Spera, Caroline Giuseppa; Lavorente, Fernanda Louise Pereira; Lorenzetti, Elis; Calasans Marques, Gustavo de [UNESP]; Almeida Freitas, Luana de; Martins, Maira Bonamin [UNESP]; Teixeira, Carlos Roberto [UNESP]; Alfieri, Amauri Alcindo; Alfieri, Alice Fernandes (Springer, 2020)
The crab-eating fox (Cerdocyon thous) is a small wild mammal present in all Brazilian biomes and in some countries of South America. This study aimed to verify the involvement of viral infectious agents in the death of a wild crab-eating fox pup (Cerdocyon thous) in Brazil. The Center for Medicine and Research of Wild Animals of the Universidade Estadual Paulista received a free-living crab-eating fox aged approximately 21 days and apparently healthy. After 13 days, the animal presented anorexia, diarrhea, fever, prostration, and neurological signs progressing to death with an inconclusive diagnosis. In a retrospective study, tissue fragments stored at - 80 degrees C were used to identify nucleic acids from major canine viruses, such as canine parvovirus-2 (CPV-2), canine adenovirus A types 1 and 2, canid alphaherpesvirus 1, and canine distemper virus. The amplified product with the expected length for CPV-2 was obtained from the heart fragment. After performing nucleotide (nt) sequencing of the amplicon, it was possible to demonstrate that the crab-eating fox strain exhibited high (99.8%) nt identity with the CPV-2b prototype (CPV-39 strain). Additionally, deduced amino acid (aa) sequence analysis showed the GAT codon for the aa Asp (D) at position 426 of the CPV-2 viral protein VP2, which characterizes the subtype 2b. To the best of the authors' knowledge, this report describes the first detection of CPV-2b DNA in tissue fragments from a crab-eating fox.
Keywords: Cerdocyon thous; Wild; Heart; CPV-2b